EASTERN AND WESTERN TRADITIONS IN UZBEK SCULPTURE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article analyzes the harmony of Western and Eastern artistic traditions in the work of representatives of Uzbekistan's schools of sculpture. Issues such as the aesthetic and philosophical foundations of Western-Eastern harmony, financial constraints, and maintaining aesthetic balance, as well as future prospects through digital platforms and international cooperation, will be discussed. This analysis highlights the place of Uzbek sculpture in the global art scene and its cultural significance.